Anti-adhesive bioresorbable elastomer-coated composite hernia mesh that reduce intraperitoneal adhesions. (January 2023) - Nikam, Shantanu P.; Hsu, Yen-Hao; Marks, Jessica R.; Mateas, Catalin; Brigham, Natasha C.; McDonald, Samantha M.; Guggenheim, Dana S.; Ruppert, David; Everitt, Jeffrey I.; Levinson, Howard; Becker, Matthew L.
Abstract: Intraperitoneal adhesions (IAs) are a major complication arising from abdominal repair surgeries, including hernia repair procedures. Herein, we fabricated a composite mesh device using a macroporous monofilament polypropylene mesh and a degradable elastomer coating designed to meet the requirements of this clinical application. The degradable elastomer was synthesized using an organo-base catalyzed thiol-yne addition polymerization that affords independent control of degradation rate and mechanical properties. The elastomeric coating was further enhanced by the covalent tethering of antifouling zwitterion molecules. Mechanical testing demonstrated the elastomer forms a robust coating on the polypropylene mesh does not exhibit micro-fractures, cracks or mechanical delamination under cyclic fatigue testing that exceeds peak abdominal loads (50 N/cm). Quartz crystal microbalance measurements showed the zwitterionic functionalized elastomer further reduced fibrinogen adsorption by 73% in vitro when compared to unfunctionalized elastomer controls. The elastomer exhibited degradation with limited tissue response in a 10-week murine subcutaneous implantation model. We also evaluated the composite mesh in an 84-day study in a rabbit cecal abrasion hernia adhesion model. The zwitterionic composite mesh significantly reduced the extent and tenacity of IAs by 94% and 90% respectively with respect to uncoated polypropylene mesh. The resulting composite mesh device is an excellent candidate to reduce complications related to abdominal repair through suppressed fouling and adhesion formation, reduced tissue inflammation, and appropriate degradation rate.